Polycyclic Aromatic Hydrocarbons in Atmospheric PM2.5 and PM10 of Riyadh City, Saudi Arabia: Levels, Temporal Variation, and Health Impacts - Hattan A. Alharbi; Ahmed I. Rushdi; Abdulqader Bazeyad; Khalid F. Al-Mutlaq (Toxics)
Background: Polycyclic aromatic hydrocarbons (PAHs) in atmospheric particulate matter (PM) are high in Saudi cities due to industry and traffic, often exceeding safety limits. This study assesses PM2.5 and PM10 and health risks in Riyadh’s desert environment. Method: High-purity chemicals and PAH standards were used. Air samples were collected at King Saud University, extracted, cleaned, and analyzed by GC-MS. QA/QC ensured accuracy, with RSDs of 4.6–7.9%. Results: Seasonal temperature shifts in Riyadh influence PM and PAH levels. Higher summer temperatures raise PM/PAH, posing health risks, especially via inhalation. Winter favors PAH accumulation on particles. Conclusions: Seasonal temperature shifts significantly affect PM2.5, PM10, and PAH levels in Riyadh, with summer posing the highest health risks. Inhalation is the main exposure route, especially for PM2.5.